2018
DOI: 10.3233/jad-180059
|View full text |Cite
|
Sign up to set email alerts
|

Change of Amyloid-β 1-42 Toxic Conformer Ratio After Cerebrospinal Fluid Diversion Predicts Long-Term Cognitive Outcome in Patients with Idiopathic Normal Pressure Hydrocephalus

Abstract: Background:Alzheimer’s disease (AD) pathology in idiopathic normal pressure hydrocephalus (iNPH) contributes to poor shunt responses. Amyloid-β 1– 42 (Aβ42) toxic conformer was recently identified with features of rapid oligomerization, strong neurotoxicity and synaptotoxicity.Objective:This observational study points to Aβ42 toxic conformer as a biomarker for AD pathology and for poor postoperative prognosis in patients with iNPH.Methods:The first cohort consisted of patients with AD (n = 17) and iNPH (n = 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Nonetheless, a significant difference in the amount of toxic conformer between AD/MCI and control groups was not observed, possibly because of the small number of samples. Indeed, Akiba et al, [87] reported significantly high levels of the toxic conformer in AD patients using our ELISA kit. They also suggested that the ratio of toxic conformer to total A42 in patients with idiopathic normal pressure hydrocephalus (iNPH) was significantly higher than control groups.…”
Section: Development Of An Anti-toxic-turn Antibody 24b3 and Its Apmentioning
confidence: 67%
“…Nonetheless, a significant difference in the amount of toxic conformer between AD/MCI and control groups was not observed, possibly because of the small number of samples. Indeed, Akiba et al, [87] reported significantly high levels of the toxic conformer in AD patients using our ELISA kit. They also suggested that the ratio of toxic conformer to total A42 in patients with idiopathic normal pressure hydrocephalus (iNPH) was significantly higher than control groups.…”
Section: Development Of An Anti-toxic-turn Antibody 24b3 and Its Apmentioning
confidence: 67%
“…For example, stroke affects functional prognosis, cancer affects life prognosis, Alzheimer's disease affects cognitive function, and Parkinson’s disease affects motor function. 208 , 274 , 280) All of these can notably affect the long-term outcomes of a shunt intervention. It is therefore good to predict the coexistence of comorbidities, such as Alzheimer's disease, using biomarkers before surgery.…”
Section: Chapter 5 Postoperative Management and Prognosismentioning
confidence: 99%
“…For postoperative follow-up, we adjusted the valve pressure and monitored proper shunt function with CSF withdrawal via valve reservoir puncture as previously reported. (7,16) If shunt malfunction was detected, the patient underwent shunt revision immediately.…”
Section: Csf Analysismentioning
confidence: 99%